Automatic Assessment- Based Artificial Intellegent to Measure Students Environmental Literacy - Yanti, Fitri April; Wardana, Rendy Wikrama; Buyung, Buyung; Heryensi, Elza; Khamis, Noorzana (Universitas Muhammadiyah Surakarta, 2025)
There is a need to measure the environmental literacy of secondary school students to promote awareness of environmental issues and provide sustainable solutions. Environmental literacy assessment is done using the UNESCO Criteria on Education and Culture Sustainable Development (ECSD). This study aimed to develop an automatic evaluation based on Artificial Intelligence (AABAI) to measure students’ environmental literacy in science subjects and environmental issues topics. This study uses the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. The data were examined through both quantitative and qualitative approaches using Item Response Theory (IRT). Content validity of the AABAI instrument was confirmed through Aiken’s V analysis, indicating acceptable validity levels. All test items were deemed valid based on the Rasch model, considering item fit and difficulty parameters. The AABAI instrument has been implemented in educational settings and has successfully provided a comprehensive overview of junior high school students’ environmental literacy profiles. The use of AABAI as a transformative assessment can ensure that students care more about the environment and maintain environmental sustainability.